Radiographic Analysis of Glenoid Morphology after Arthroscopic Latarjet vs Distal Tibial Allograft in the Treatment of Anterior Shoulder Instability. Issue 7 (30th July 2018) - Wong, Ivan H.; King, JP; Boyd, Gordon; Mitchell, Michael; Coady, Catherine M.
Objectives: The Latarjet procedure for autograft transposition of coracoid to the anterior rim of the glenoid remains the most common procedure for reconstruction of the glenoid after shoulder instability. The anatomic glenoid reconstruction using distal tibial allograft has gained popularity and is suggested to better match the normal glenoid size and shape. However, there is concern for decreased healing and increased resorption using an allograft bone. The purpose of this study was to evaluate the arthroscopic reconstruction of the glenoid with respect to the size, shape, healing, and resorption of autograft coracoid vs allograft distal tibia. Methods: A retrospective review of 50 consecutive patients who had an arthroscopic boney reconstruction of the glenoid (13 coracoid; 37 distal tibial), diagnosed with anterior shoulder instability, and CT confirmed glenoid bone loss >20%. Pre-and post-operative CT scans were reviewed by two fellowship trained musculoskeletal radiologists for: graft position, glenoid concavity, cross sectional area, width, version, total area, osseous union, and graft resorption. Results: Graft nonunion was seen in 3 (23.07%) of the coracoid patients, and in 2 (5.4%) of the tibial allograft patients (OR 5.25; 95% CI: 0.768-35.89). Odds ratios comparing allograft to coracoid for overall resorption was 5.00 (CI: 1.276-19.597). Graft resorption greater than 50% was seen in 3 (8.11%) of the allografts and was absent within the coracoid patients. Graft resorption lesser than 50% was greater in both groups with 27 (72.97%) allograft and 6 (46.15%) coracoid patients. However, no statistically significant difference was found between the two procedures regarding AP diameter of graft (p=0.818) or graft cross sectional area (p=0.797). Conclusion: Arthroscopic anatomic glenoid reconstruction using distal tibial allograft showed greater boney union but higher resorption compared to coracoid autograft. Even so, there was no statistically significant difference between the two procedures regarding final graft surface area and size of grafts. These short-term results suggest distal tibial allograft as an alternative to coracoid autograft in the recreation of glenoid boney morphology.